Pair density wave and superconductivity in a kinetically frustrated doped Emery model on a square lattice - Jiang, Hong-Chen; Devereaux, Thomas Peter (Frontiers in Electronic Materials, 2023)
The quest to understand the nature of superconductivity in the cuprates has spotlighted the pair density wave (PDW) -a superconducting state characterized by a spatially modulated order parameter. Despite significant advances in understanding PDW properties, conclusively demonstrating its presence in systems pertinent to cuprate superconductors remains elusive.In this study, we present a systematic density-matrix renormalization group study to investigate the Emery model (or the three-band Hubbard model) on two-leg square cylinders with negative electron hopping term t pp between adjacent oxygen sites. Kinetic frustration -introduced by changing the sign of oxygen-oxygen hopping -leads to a much reduced Cu-Cu antiferromagnetic exchange along with an enlarged charge transfer energy that changes the local properties of the model. At light doping levels, our findings reveal a ground state remarkably consistent with a PDW, exhibiting mutually commensurate superconducting (SC), charge and spin density wave correlations. Intriguingly, the dominant SC pairing is observed between neighboring oxygen sites, diverging from the expected Cu sites in the positive t pp case. When the system incorporates moderate near-neighbor interactions, particularly an attractive V pp between adjacent oxygen sites, the SC correlations become quasi-long-ranged, accompanied by a pronounced divergence in the PDW susceptibility. When further increase the attractive V pp , the system gives ways to an unconventional d-wave superconductivity.